Utility of Blood Cultures in Healthy Children with a History of Fever Presenting to the Emergency Department: A Comparison of Afebrile Versus Febrile on Presentation - Jeannette Dodson; Mohamed Badawy; McElvania Tekippe; Halim Hennes (Journal of Pediatric Emergency and Intensive Care Medicine, 2021)

(untitled)
Introduction:Blood cultures are often obtained from healthy paediatric patients with fever on presentation to the emergency department (ED). Although published guidelines and previous research outlined indications for obtaining blood culture and the relatively low risk of bacteraemia in vaccinated children, there may be practice variability among institutions and physicians. Primary objective: To describe the demographic characteristics, diagnosis, disposition and outcome of children who are fully vaccinated, healthy and have fever from whom bacterial blood cultures were obtained. Secondary objective: To determine the rate of blood culture contamination and outcomes.Methods:Retrospective chart review of all blood cultures collected in the ED between January 1, 2015, and December 31, 2015. Patients aged 6 months to 17 years were eligible for enrolment. Children not fully vaccinated, immunocompromised or with chronic, debilitating disease were excluded. Patients were divided into febrile and afebrile cohorts based on the initial temperature at ED presentation. Data were analysed with two-sample t-test and chisquared analysis.Results:Blood cultures were obtained from 7.980 children at the ED, with an overall positivity rate of 5.51%. No significant difference was detected in the number of positive blood cultures between the two cohorts (p=0.85). No significant difference was found between pathogenic cultures between the two cohorts (p=0.35). All patients who were discharged with a positive blood culture were called back for a repeat culture. None grew a pathogenic organism on the repeat culture. The overall positive blood culture rate for true pathogens was 1.3%, and the overall contamination rate was 1.9%.Conclusion:The rates of positive blood culture between febrile and afebrile cohorts presenting to the ED were comparable. While the overall rate of positive culture remains low, consistent with previously reported rates of bacteraemia, an unacceptably high rate of contamination resulting in return visits was observed. Routine blood culture in children who were fully immunised and had a history of febrile illness is not indicated.